Simultaneous Measurement of Air Pressure and Temperature Using Fiber-Optic Cascaded Fabry–Perot Interferometer - Zhigang Li; Jiajun Tian; Yuzhu Jiao; Yunxu Sun; Yong Yao (IEEE Photonics Journal)
We propose and demonstrate a fiber-optic cascaded-cavity Fabry–Perot interferometer (FPI) for simultaneous measurement of air pressure and temperature. The open-cavity hybrid FPI consists of an air-cavity and a silica-cavity formed by a section of silica tube and photonic crystal fiber, respectively. The air-cavity and silica-cavity exhibit different sensitivities to air pressure and temperature. Thus, the proposed sensor can be used to implement air pressure and temperature sensing simultaneously. The spectra of the air-cavity and silica-cavity are extracted from the total reflection spectrum with designed bandpass filters. The air pressure and temperature sensitivities of the air-cavity are 4.04 pm/kPa and 0.87 pm/°C, respectively, and those of the silica-cavity are 3.36 pm/kPa and 14.36 pm/°C, respectively. Moreover, the temperature and air pressure cross-sensitivity can be reduced by using a sensitivity coefficients matrix of two cavities. With the advantages of compact size, easy fabrication, and all-fiber structure, the proposed sensor is a potential candidate for practical applications.